Chapter Mezzogiorno e fascismo - ZOPPI, Sergio (Studi e saggi, 2021)
The relationship between Southern Italy and fascism is a little explored theme. The contribution reflects on this subject presenting unpublished conclusions: it starts from a volume by the author named after the monthly magazine 'Il Saggiatore' (Naples 1924-1925) by Gherardo Marone and expands the reflection through a more recent book by Zoppi dedicated to the magazine 'Questioni meridionali', also published in Naples, from 1934 to 1943. The three editors of 'Questioni meridionali' - Giuseppe Cenzato, an entrepreneur who was also the soul of the company, Francesco Giordani, a young chemical scientist, and Gino Olivetti, a politician and industrialist - despite being fascists, they created a periodical that showed how the 'Southern question', never mentioned by the dictatorship, remained, however, alive in its tragic backwardness. Every year, two large issues of the magazine were released, characterized by one or more original studies and always accompanied by extensive bibliographic reviews. Among the topics, analysed by a group of highly qualified scholars and often in comparison with the North of Italy, the following emerged: the railway network, tourism, the demographic and health situation, the birth rate, the difficulties of the construction industry, ports, the economic and production context. The magazine pays particular attention to the city of Naples and its housing drama and to the southern tax system, a primary source of backwardness starting with the problem of local government.